A Predictor Combining Clinical and Genetic Factors for AML1-ETO Leukemia Patients - Yang, Min; Zhao, Bide; Wang, Jinghan; Zhang, Yi; Hu, Chao; Liu, Lixia; Qin, Jiayue; Lou, Feng; Cao, Shanbo; Wang, Chengcheng; Yu, Wenjuan; Tong, Hongyan; et al. (Frontiers in Oncology, 2022)
CBF-AML is one of the most common somatic mutations in acute myeloid leukemia (AML). t(8; 21)/AML1-ETO-positive acute myeloid leukemia accounts for 5-10% of all AMLs. In this study, we consecutively included 254 AML1-ETO patients diagnosed and treated at our institute from December 2009 to March 2020, and evaluated molecular mutations by NGS 185-gene platform to explore genetic co-occurrences with clinical outcomes. Our results showed that high KIT VAF(≥15%) correlated with shortened overall survival compared to other cases with no KIT mutation. However, no difference was found in patients’ OS (3-year OS rate 26.6% vs 59.0% vs 69.6%, HR 1.50, 95%CI 0.78-2.89, P=0.0005) whether they have KIT mutation in two or three sites. Additionally, we constructed a risk model by combining clinical and molecular factors; this model was validated in other independent cohorts. In summary, our study showed that c-kit other than any other mutations would influence the OS in AML1-ETO patients. A proposed predictor combining both clinical and genetic factors is applicable to prognostic prediction in AML1-ETO patients.